(3NGJeI aj GdJUhas - (3CMeO RQhb HdYeT,J (B1247 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3eGbOefGg JhMjO GdeJcdejf hgh EaQGO GdJhMjO eY YOe GdYed HebJVGg hCeG JhMjO GdYGQajf hgh GdJUha agh GdYed HebJVi GdJhMjO MJi dGjdJaJ Edi GdNdb s
(3BNQgG (B:s
(3EPG VGa GdYeQ hGdhbJ hHGdCehQ GdeYdb YdjgG MSf GdNGJeI QRbfG Gdgd EjGg Hefi hcQeg hUdi Gddg Ydi SjOfG eMeO Udi Gddg Ydjg hSde Bdg hUMHg GfJgJ GdNGJeI s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI CMeO QRhb hdO HdYeS GdNGUI HfhGcThW s
Keywords: (3GdJUha hGdBOGH GdTQYjIs